Three Mountains to Freedom - Davies, John Dudley (Practice Interpretation, 2016)
In Galatians, we meet Paul at his most passionate, most personal, and his most political. For him, the heart of the Gospel is: The Son of God who loved me and gave himself for me. But for some of his colleagues, faith in Christ is not enough. They want something that will give more of a sense of achievement; they yearn for the more exclusive insignia of the Jewish law. Senior church leaders are confused and compromised. Paul faces this crisis with two further essentials of the Gospel, our unity in Christ and our freedom in Christ. The book shows how, in our own day, the same testing of faith happens, with issues of race, gender, poverty, equality, in a culture which values the achievements of some while treating others with disdain. Written geographically from a Welsh context, this is the Archbishop of Wales's recommended Lent book for 2016; but it speaks to the wider motivations of our present culture. For the author, Galatians was a primary weapon in the theological struggle against the ideology of apartheid in South Africa; it has a similar relevance for today's Britain and beyond.